2021
DOI: 10.1051/shsconf/202110703002
|View full text |Cite
|
Sign up to set email alerts
|

The lack of reversibility during financial crisis and its identification

Abstract: The focus of this study to measure the varying irreversibility of stock markets. A fundamental idea of this study is that financial systems are complex and nonlinear systems that are presented to be non-Gaussian fractal and chaotic. Their complexity and different aspects of nonlinear properties, such as time irreversibility, vary over time and for a long-range of scales. Therefore, our work presents approaches to measure the complexity and irreversibility of the time series. To the presented methods we include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…We have performed RQA under sliding window procedure for standardized returns and standardized initial time series [33,34,35,36,37,38]. We have found that standardized initial time series better expresses internal complexity and recurrent properties of the energy market indices.…”
Section: Results and Analysismentioning
confidence: 99%
“…We have performed RQA under sliding window procedure for standardized returns and standardized initial time series [33,34,35,36,37,38]. We have found that standardized initial time series better expresses internal complexity and recurrent properties of the energy market indices.…”
Section: Results and Analysismentioning
confidence: 99%
“…The paper "High-order network analysis for financial crash identification" by Andrii O. Bielinskyi, Vladimir N. Soloviev, Serhii V. Hushko, Arnold E. Kiv, and Andriy V. Matviychuk [46] proposes to use high-order networks to study the temporal evolution of the Dow Jones Industrial Average (DJIA) index. The paper begins by discussing the importance of network analysis for understanding the complexity and dynamics of socio-economic systems.…”
Section: Articles Overviewmentioning
confidence: 99%
“…It is worth noting that there are also various algorithms for converting a time series to a graph. We would like to emphasize the visibility graph algorithms [14,17,55,64,93] (figure 5) and one based on recurrence analysis [35] (figure 6).…”
Section: Network Analysismentioning
confidence: 99%
“…Over the past decade, various methods have been proposed for calculating the degree of irreversibility in systems [26,30,34,41,54,59,65,105] and we have presented how to use some of them for crises identification [14]. For pedagogical purposes, along with the mentioned concept of multifractality and entropy, we would like to present irreversibility based on the multifractal approach [54] and permutation patterns [105].…”
Section: Reversibility and Irreversibilitymentioning
confidence: 99%